An artificial intelligence (AI) approach to disk drive failure analysis - Tan, Choon Eng. (2009)
In high volume hard disk manufacturing, the ability to stay profitable depends very much on the factory to turnaround every product to finished goods as quickly as possible. Ways and means to do so is one of the main focus in this manufacturing sector. Besides trying to reduce cycle time at each build and test station, one other area of focus is to speed up the rework process of failed drives, which is dependent on how accurate and fast the failed drives can be diagnosed.